2009
DOI: 10.1292/jvms.71.319
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of the Spinal Cord of C57BL/6J Mice Infected with Rabies Virus (CVS-11 Strain)

Abstract: ABSTRACT. Fixed rabies viruses (CVS-11 strain) were inoculated intramuscularly to C57BL/6J mice, and the pathomorphological changes of the spinal cord including dorsal root spinal ganglion cells were investigated. At 4 days postinoculation (PI), viral antigens were first detected in the spinal neurons and dorsal root spinal ganglion cells without producing morphological changes. At 5 days PI, mild infiltration of lymphocytes was observed around the central canal, small blood vessels and leptomeninges. Cells po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…CVS strain of fixed RABV in suckling, neonatal and adult mice produces encephalitis with marked neuronal apoptosis in various regions of brain when inoculated intracerebrally [15,16]. In contrast, peripheral routes of inoculation of CVS in adult mice showed severe and fatal encephalitis without prominent neuronal apoptosis [3,13,[17][18][19].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…CVS strain of fixed RABV in suckling, neonatal and adult mice produces encephalitis with marked neuronal apoptosis in various regions of brain when inoculated intracerebrally [15,16]. In contrast, peripheral routes of inoculation of CVS in adult mice showed severe and fatal encephalitis without prominent neuronal apoptosis [3,13,[17][18][19].…”
Section: Discussionmentioning
confidence: 97%
“…However, in rabies the T cell response was found inefficient being inactivated by the virus [2,12]. Further, cells undergoing death were leukocytes and not neurons, which were confirmed by immunohistochemical studies [2,3,[12][13][14]. The CVS strain of RABV by intracerebral route in mice produces encephalitis with marked neuronal apoptosis [15,16], whereas peripheral routes of inoculation produces severe and fatal encephalitis without prominent neuronal apoptosis [3,13,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry: For detection of rabies virus antigens in tissues, all sections were stained using the streptavidin-biotin-peroxidase complex method using anti-rabbit phosphoprotein (P) [15]. For detection of cell type, the following primary antibodies were used: anti-glial fibrillary acidic protein (GFAP) for astroglial cells (Nichirei Biosciences, Tokyo, Japan); anti-ionized calcium binding adaptor molecule 1 (Iba1) for microglial cells (Wako, Osaka, Japan); anti-CD3 for T lymphocytes (DAKO, Kyoto, Japan); and anti-CD20 for B lymphocytes (Spring Bioscience, Fremont, CA, U.S.A.).…”
Section: Virus Mice and Viral Inoculationmentioning
confidence: 99%
“…Previously, we demonstrated that C57BL/6J mice inoculated intramuscularly with CVS-11 showed paralysis with severe spinal lesions [15]. The spinal lesions were composed of the infiltration of T lymphocytes, the increase of microglial cells and astroglial cells and the majority of T lymphocytes exhibited apoptosis.…”
mentioning
confidence: 90%